Experimental and thermodynamic assessment of the La–Ti and La–Zr systems. (March 2016) - Mattern, N.; Yokoyama, Y.; Mizuno, A.; Han, J.H.; Fabrichnaya, O.; Richter, M.; Kohara, S.
Abstract: The phase equilibria of the binary La–Ti and La–Zr system have been investigated between 900 K and 2300 K by combining conical nozzle levitation technique with in situ high energy synchrotron X-ray diffraction. The coexistence ranges of phases as well as experimental data of the liquidus and binodal line were obtained from the analysis of the diffraction data. The monotectic character of the La–Ti system is evident by the occurrence of two diffuse diffraction maxima according to the coexistence of two liquids above the monotectic temperature of 1845 K±20 K. The La–Zr phase diagram is a eutectic type, owning a metastable miscibility gap with a critical temperature close to the liquidus temperature. Based on the experimental data, thermodynamic descriptions of the La–Ti and La–Zr phase systems were derived. Graphical abstract: Highlights: The La–Ti and La–Zr systems were experimentally assessed. In situ XRD was combined with levitation to study liquid phase equilibria. The monotectic character of La–Ti phase diagram was confirmed. The eutectic-like La–Zr system owns a metastable miscibility gap. Thermodynamic descriptions of the La–Ti and La–Zr were derived.